Realizing Adaptive Justice: UKT Relief Reform and the Implementation of Force Majeure at UIN SGD Bandung - Husnul Rizka Mubarikah (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper conducts an in-depth study of the failure of the Single Tuition Fee (UKT) relief policy at UIN Sunan Gunung Djati Bandung in realizing adaptive justice for students experiencing sudden economic difficulties. The main issue is the rigidity of internal regulations that lack a responsive mechanism (force majeure) to changes in financial conditions mid-semester, leaving students vulnerable to the risk of dropping out of their studies. This study uses qualitative policy analysis methods, including problem identification (USG), determining the root cause, and evaluating alternatives using the William N. Dunn scoring model. The analysis identifies three structural root causes: (1) Rigid Regulations that ignore incidental crises; (2) Budgetary Focus on UKT Revenue Stability, which limits flexibility; and (3) Bureaucratic Pressure to maintain a high revenue efficiency ratio, causing a shift in the goal from equity to efficiency. Based on the alternative evaluation, policy recommendations prioritize integrated regulatory solutions. UIN SGD Bandung is recommended to issue a Rector's Decree on Adaptive Force Majeure UKT to create a fast verification path. This policy must be operationally supported through Risk-Based Digital Verification Regulations to reduce administrative and bureaucratic burdens. Implementing these regulatory reforms is crucial to balance the financial interests of institutions with their social mandates, ensure the continuity of studies for students from low-income families, and end disparities in access to equitable education.